(untitled) (LACCEI, 2024)
The Chilintomo irrigation system serves an area of ​​2000 ha and has been in operation since the 1970s. The diversion structure worked with a dam with planks, which were placed when the winter season ended to take advantage of the low water flows. In 2016 the structure was "repowered" by implementing a 3 m concrete dam however, this has caused problems with flooding upstream of it. This research aims to cover the use of inflatable dams in agriculture, analyzing the case study of the Chilintomo River - Ecuador, which allows the free passage of maximum flows in the rainy season and in turn allows controlling the levels in the channel in dry season, The methodological process contemplated the collection of meteorological and cartographic data, information processing, modeling and design proposal, in order to establish a runoff rain model using HEC - HMS, analysis and results of the hydraulic model with two scenarios of the inflatable gate. The results obtained from the modeling show that the structure allows to mitigate the floods that produce the maximum flows for the low return periods, and in dry season it will be able to divert the flows towards the irrigation channels of the system. The implementation of agri-food systems is part of the 17 Sustainable Development Goals (SDG) (1, 2, 9, 15, 16 and 17), proposed by the United Nations (UN) in 2015.